Attitudes and Beliefs Toward Computerized Cognitive Training in the General Population - Goghari, Vina M.; Krzyzanowski, Daniel; Yoon, Sharon; Dai, Yanni; Toews, Deanna (Frontiers in Psychology, 2020)
Introduction In recent years, computerized cognitive training (CCT) programs have been developed commercially for widespread public consumption. Despite early enthusiasm, whether these programs enhance cognitive abilities in healthy adults is a contentious area of investigation. Given the mixed findings in the literature, researchers are beginning to investigate how beliefs and attitudes toward CCT impact motivation, expectations, and gains after cognitive training. Method We collected survey data from 497 North American participants from Amazon’s Mechanical Turk (MTurk). This survey asked novel questions regarding respondents’ beliefs about the effectiveness of CCT for improving different domains of cognition, mood, and daily life; beliefs about whether CCT programs are supported by research; and whether impressions of CCT have improved or worsened over time. Exploratory analyses are reported descriptively, while parametric tests were used to analyze a priori hypotheses. Results Almost half of the surveyed participants had used CCT, and respondents with a self-reported psychological or neurological disorder were more likely to have used CCT platforms than participants without such conditions. Motivations for using CCT included curiosity; to improve or maintain cognition; to prevent cognitive decline; and/or for enjoyment or fun. Participants believed that CCT is somewhat effective for improving mood and cognition across a variety of domains. Greater age and fewer years of education predicted perceived effectiveness of CCT. Finally, participants largely reported unchanged opinions of CCT platforms over time. Conclusion Our study suggests the need for future research regarding the general population’s beliefs and attitudes toward CCT, along with knowledge translation for relevant stakeholders.